PRODUKSI BIOGAS DARI LIMBAH KOTORAN SAPI PERAH DENGAN REAKTOR BIOGAS SISTEM BATCH DI DESA LEREP KABUPATEN UNGARAN - Didik Wisnu Widjajanto; Heny Kusumayanti; Sri Rejeki (METANA, 2021)
Abstract   Biogas is mixed gas of methane(CH4),  carbondioxide (CO2) and others which is produced as a result of moterial degradation of organic material such as animal and humon feces or plant byproduct by methanagen bacterial activity in biodigester. The present work is aimed to produce biogas fromfeces of milk cow. Biogas reactor used is built by IbM team of "IbM Peternak sapi Perah Penghasil Biogas di larep-Ungaran" (batch system). Result of present work revealed that 4 m3 biogas reactor with batch system is able to produce biogas starting doy 4. ln the following day, the biogas production increase and reach peak on day seven which is produce 42,85 liter of mix gas or 25,71 liter of methana gas   Keywords : biogas. batch system, cow feces http://ejournal.undip.ac.id/index.php/metana/editor/viewMetadata/1643